1974
DOI: 10.1029/ja079i028p04239
|View full text |Cite
|
Sign up to set email alerts
|

Midday Pc 1-2 pulsations observed at a subcleft location

Abstract: A class of unstructured Pc 1–2 pulsation activity, as identified on Bar I (70.2°N) records taken during 1968–1972, is found to be present in midday hours on about half of the days in summer months. The events have some tendency to occur in the later part of the ring current recovery phase, especially at times of moderate AE when the cleft lines are just poleward of Bar I. The source lines of the Pc 1–2 are found to lie essentially outside the plasmapause. In terms of the proton cyclotron resonance instability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

1975
1975
1996
1996

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…In conclusion, we believe that most of our observed wave events suggest that ion cyclotron waves are being generated in the outer magnetosphere, consistent with ground observations by Heacock [ 1974] and Feigin et al [ 1978]. In addition, the few intervals of right-hand-polarized waves seen in Figure 6 suggest that a second source of Pc 1-2 waves other than ion cyclotron resonance must exist.…”
Section: The Three Intervals Onsupporting
confidence: 92%
“…In conclusion, we believe that most of our observed wave events suggest that ion cyclotron waves are being generated in the outer magnetosphere, consistent with ground observations by Heacock [ 1974] and Feigin et al [ 1978]. In addition, the few intervals of right-hand-polarized waves seen in Figure 6 suggest that a second source of Pc 1-2 waves other than ion cyclotron resonance must exist.…”
Section: The Three Intervals Onsupporting
confidence: 92%
“…A 4-s band does not appear very often in our data; neither does it appear any more consistently than other short-lived frequency bands. These results are to be expected, however, because the activity in the 4-s band is predominantly a high-latitude phenomenon and it has pronounced seasonal variation with a maximum in summer [Heacock, 1966[Heacock, , 1974. Our mid-latitude observations were made at the end of winter, when the hourly occurrence rates of 4-s activity measured by Heacock [1966] were a factor of 10 less than those in summer.…”
Section: Figure 1 Shows a Complete 24-hour Series Of Hourly Averagementioning
confidence: 50%
“…Pulsations in this period range have also been classified into two main categories according to whether they exhibit structures with frequency rising with time (structured) or not (unstructured) [Heacock and Akasofu, 1973]. Investigations have shown that structured Pc1 pulsations are typical at low and middle latitudes [Webster and Fraser, 1985], while unstructured Pc I pulsations occur mostly at high latitudes [Heacock, 1974;Arnoldy et al, 1988]. Considering the close similarity that often prevails between Pc 1 and Pc 2 pulsations, it is questionable whether the separation into these two classes with a transition at a period of 5 s has any physical significance.…”
Section: Introductionmentioning
confidence: 99%